2018
DOI: 10.1111/ggi.13552
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel convenient Alzheimer's disease assessment scale, the ABC Dementia Scale, using item response theory

Abstract: Aim The present study aimed to assess the interrater reliability and construct the validity of a novel, convenient informant‐based Alzheimer's disease assessment scale to prepare its final version. Methods For the assessment, site investigators, co‐medicals and, if available, medical staff other than doctors or co‐medicals interviewed study informants to assess individuals using this scale. We then analyzed the interrater reliability and construct validity using factor analysis and item response characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The MHLW cognitive function scores also had an excellent inter-rater reliability, MHLW as indicated by a kappa coefficient of 0.62, Cronbach’s α of 0.87, and intraclass correlation coefficient 0.78. The MMSE [ 18 ] and ABC Dementia Scale [ 19 ] are existing measures of cognitive function that have been reported to have good inter-rater reliabilities, as shown by a kappa coefficient of 0.98 and weighted kappa coefficient of 0.75, respectively [ 7 ]. However, the MMSE consists of 11 items, including drawing pictures [ 7 ], and the ABC Dementia Scale of 13 items [ 19 ], which makes these measures cumbersome to use in extremely busy clinical settings in Japan, such as acute care hospitals or for mass screenings [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MHLW cognitive function scores also had an excellent inter-rater reliability, MHLW as indicated by a kappa coefficient of 0.62, Cronbach’s α of 0.87, and intraclass correlation coefficient 0.78. The MMSE [ 18 ] and ABC Dementia Scale [ 19 ] are existing measures of cognitive function that have been reported to have good inter-rater reliabilities, as shown by a kappa coefficient of 0.98 and weighted kappa coefficient of 0.75, respectively [ 7 ]. However, the MMSE consists of 11 items, including drawing pictures [ 7 ], and the ABC Dementia Scale of 13 items [ 19 ], which makes these measures cumbersome to use in extremely busy clinical settings in Japan, such as acute care hospitals or for mass screenings [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MMSE [ 18 ] and ABC Dementia Scale [ 19 ] are existing measures of cognitive function that have been reported to have good inter-rater reliabilities, as shown by a kappa coefficient of 0.98 and weighted kappa coefficient of 0.75, respectively [ 7 ]. However, the MMSE consists of 11 items, including drawing pictures [ 7 ], and the ABC Dementia Scale of 13 items [ 19 ], which makes these measures cumbersome to use in extremely busy clinical settings in Japan, such as acute care hospitals or for mass screenings [ 5 ]. In contrast, cognitive function scores are simpler and easier-to-use, while also having sufficient reliability for use in mass screening or busy clinical settings, despite their slightly lower inter-rater reliability than the MMSE and ABC Dementia Scale.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research on the concurrent validity of ABC-DS with standard assessment scales [26] found that the correlation was 0.67, -0.64, 0.70, and -0.83 between ABC-DS scores for ADL, BPSD, CF, and TDD and 1) the corresponding scales in the Disability Assessment for Dementia (DAD), 2) the Neuropsychiatric Inventory (NPI), 3) the MMSE, and 4) Clinical Dementia Rating sum of boxes (CDR-SOB), respectively. Also, the intraclass correlation coefficient of the TDD score was 0.96, which was determined by evaluating scores measured at baseline, and those taken one week later [27].…”
Section: Abc-dsmentioning
confidence: 99%
“…We have previously validated a brief assessment scale-the "ABC Dementia Scale" (ABC-DS)-which can concurrently evaluate ADL, BPSD, and CF in ten minutes on average [26][27][28]. We developed a novel algorithm for this scale called the three-dimensional distance (TDD), for estimating the overall severity of each state while taking into account the fact that ADL, BPSD, and CF levels should explain a patient's disease condition.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid aging of the population in Japan, the numbers of patients with dementia will increase in the coming years. It is estimated that the number of elderly patients with dementia will rise from 4.62 million in 2012 to 7.3 million in 2025, at which time approximately 1 in 5 individuals aged 65 years or older will be affected by this disease [1].…”
Section: Introductionmentioning
confidence: 99%